1981
DOI: 10.1093/oxfordjournals.jbchem.a133261
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Method for Homolysis with a Hypoxanthine-Xanthine Oxidase System and Alteration of Erythrocyte Phospholipid Composition during the Hemolysis

Abstract: A very rapid hemolysis was found to be caused by active oxygen species produced by a hypoxanthine-xanthine oxidase system with very low concentrations of hypoxanthine. The addition of superoxide dismutase or catalase inhibited the hemolysis, indicating that O2- and H2O2 participate in this system. The extent of erythrocyte hemolysis was found to depend on the sex of the human donor. The change in phospholipid composition before and after hemolysis in human erythrocytes from donors of each sex was compared by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…There are many reports concerning the structural changes of biological membranes induced by active oxygen species. In some studies human erythrocytes were used as a target for active oxygen (Taniguchi et al, 1981). In vitro studies have also indicated that free radical producing agents such as tertbutyl hydroperoxide (tBH) and hydrogen peroxide (H 2 O 2 ) are able to oxidize membrane lipids from liver hepatocytes and to produce the lipid peroxidation product malondialdehyde (MDA) or to cause red blood cell haemolysis (Joyeux et al, 1990;Liu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports concerning the structural changes of biological membranes induced by active oxygen species. In some studies human erythrocytes were used as a target for active oxygen (Taniguchi et al, 1981). In vitro studies have also indicated that free radical producing agents such as tertbutyl hydroperoxide (tBH) and hydrogen peroxide (H 2 O 2 ) are able to oxidize membrane lipids from liver hepatocytes and to produce the lipid peroxidation product malondialdehyde (MDA) or to cause red blood cell haemolysis (Joyeux et al, 1990;Liu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a system with the capacity to generate superoxide radicals and H2O2 can cause hemolysis of RBCs (16,17). In agreement with this view, the fact that hemolysis has been induced only in the vitamin E-deficient RBCs by xanthine oxidase reaction, but not in vitamin E-sufficient ones, indicates RBC damage resulting from membrane peroxidation.…”
mentioning
confidence: 71%
“…The effects of exposure to hypoxanthine and xanthine oxidase on erythrocytes as regards hemolysis were studied by earlier authors (10,11,19). The reported results were somewhat conflicting.…”
Section: Discussionmentioning
confidence: 99%